2018
DOI: 10.15414/jmbfs.2018.7.6.571-575
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CULTIVATION CONDITIONS ON ACTIVITY OF Α-Amylase FROM a TROPICAL STRAIN ASPERGILLUS FLAVUS LINK

Abstract: An important integral part of the physiology of the fungal cell is the nature of the cascade of extracellular enzymes produced by fungi. A tropical strain Aspergillus flavus Link obtained from deteriorated tomato (Solanum lycopersicum) fruits grew in a growth nutrient medium composed of MgSO4.7H20, K2HPO4, KH2PO4, FeSO4.7H2O, potassium nitrate and starch at 30oC. Extracellular proteins produced by the isolate in the medium expressed α-amylase activity. The enzyme was partially purified by ammonium sulphate pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…On the effect of pH and temperature on the activity of the α-amylase enzyme produced by Aspergillus niger FAB-211, using a culture medium containing maltose and yeast extract Asrat and Girma (2018) identified a maximum activity at pH 6 and a temperature of 45º C. This same pH value for better enzyme activity was also found when α-amylase was produced by other fungi of the Aspergillus genus. When checking the effect of pH on the α-amylase activity produced by Aspergillus oryzae, using residual water with starch, Shah et al (2014) found a maximum activity for the enzyme at pH 6 and a temperature of 50º C. While Adejuwon, Tsygankova and Alonge (2018) found a maximum activity of α-amylase produced by Aspergillus Flavus Link, with a nutritive culture medium composed of MgSO4.7H20, K2HPO4, KH2PO4, FeSO4.7H2O, potassium nitrate and starch at pH 6 and temperature 35º C. Therefore, there is a variation in the optimum pH and the optimum activity temperature of the α-amylase produced.…”
Section: Resultsmentioning
confidence: 99%
“…On the effect of pH and temperature on the activity of the α-amylase enzyme produced by Aspergillus niger FAB-211, using a culture medium containing maltose and yeast extract Asrat and Girma (2018) identified a maximum activity at pH 6 and a temperature of 45º C. This same pH value for better enzyme activity was also found when α-amylase was produced by other fungi of the Aspergillus genus. When checking the effect of pH on the α-amylase activity produced by Aspergillus oryzae, using residual water with starch, Shah et al (2014) found a maximum activity for the enzyme at pH 6 and a temperature of 50º C. While Adejuwon, Tsygankova and Alonge (2018) found a maximum activity of α-amylase produced by Aspergillus Flavus Link, with a nutritive culture medium composed of MgSO4.7H20, K2HPO4, KH2PO4, FeSO4.7H2O, potassium nitrate and starch at pH 6 and temperature 35º C. Therefore, there is a variation in the optimum pH and the optimum activity temperature of the α-amylase produced.…”
Section: Resultsmentioning
confidence: 99%
“…α-Amylase activity was assayed using the modified method of Pfueller & Elliott [20] and Adejuwon et al [22]. The reaction mixture was 2 mL of buffered (0.02m citrate phosphate buffer pH 6.0), soluble starch (Sigma) and 0.5 mL enzyme.…”
Section: α-Amylase Assay In Crude Enzymementioning
confidence: 99%